Evidence Suggesting that the Cardiomyocyte Circadian Clock Modulates Responsiveness of the Heart to Hypertrophic Stimuli in Mice - Durgan, David J. (2011)
Circadian dyssynchrony of an organism (at the whole body level) with its environment, either through light/dark cycle or genetic manipulation of clock genes, augments various cardiometabolic diseases. The cardiomyocyte circadian clock has recently been shown to influence multiple myocardial processes, ranging from transcriptional regulation and energy metabolism, to contractile function. We therefore reasoned that chronic dyssychrony of the cardiomyocyte circadian clock with its environment would precipitate myocardial maladaptation to a circadian challenge (simulated shift work; SSW). To test this hypothesis, 2 and 20 month old wild-type and CCM (Cardiomyocyte Clock Mutant; a model with genetic temporal suspension of the cardiomyocyte circadian clock at the active-to-sleep phase transition) mice were subjected to chronic (16-wks) bi-weekly 12-hr phase shifts in the light/dark cycle (i.e., SSW). Assessment of adaptation/maladaptation at whole body homeostatic, gravimetric, humoral, histological, transcriptional, and cardiac contractile function levels revealed essentially identical responses between wild-type and CCM littermates. However, CCM hearts exhibit increased bi-ventricular weight, cardiomyocyte size, and molecular markers of hypertrophy (anf, mcip1) independent of aging and/or SSW. Similarly, a second genetic model of selective temporal suspension of the cardiomyocyte circadian clock (Cardiomyocyte-specific BMAL1 Knockout [CBK] mice) exhibits increased bi-ventricular weight and mcip1 expression. Wild-type mice exhibit 5-fold greater cardiac hypertrophic growth (and 6-fold greater anf mRNA induction) when challenged with the hypertrophic agonist isoproterenol at the active-to-sleep phase transition, relative to isoproterenol administration at the sleep-to-active phase transition. This diurnal variation was absent in CCM mice. Collectively, these data suggest that the cardiomyocyte circadian clock likely influences responsiveness of the heart to hypertrophic stimuli.